2014
DOI: 10.1007/s10967-014-3358-9
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 97Ru from niobium target using PEG based aqueous biphasic systems

Abstract: Separation of no-carrier-added (NCA) 97 Ru from bulk niobium target has been carried out for the first time using green analytical technique, aqueous biphasic system. 50 % (w/v) polyethylene glycol (PEG)-4000, against 2 M solutions of various salts such as Na-citrate, and 4 M KOH were employed at room temperature for the extraction of NCA 97 Ru from bulk niobium. Influence of molecular weight of PEG rich phase as well as pH of some salt rich phase (e.g., Na-tartarate) on the extraction behaviour of NCA 97 Ru i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…nat Y [63]. In both the cases the target is monoisotopic in nature, i.e., 93 Nb and 89 Y have 100 % natural abundance. It has been found for 7 Li-induced reaction that below 32 MeV projectile energy contaminations from other coproduced radionuclides are negligible.…”
Section: Protocol and Physics Of Heavy Ion Activationmentioning
confidence: 98%
See 2 more Smart Citations
“…nat Y [63]. In both the cases the target is monoisotopic in nature, i.e., 93 Nb and 89 Y have 100 % natural abundance. It has been found for 7 Li-induced reaction that below 32 MeV projectile energy contaminations from other coproduced radionuclides are negligible.…”
Section: Protocol and Physics Of Heavy Ion Activationmentioning
confidence: 98%
“…= 2.44 MeV) is useful in positron emission tomography, 95 Tc (T 1/2 = 20 h) is important in monitoring slow metabolic functions of brain and heart, etc. Following the protocol, for the first time we have investigated heavy ion induced production route of neutron deficient 93,94,95 Tc radionuclides by bombarding 9 Be on natural yttrium target ( 89 Y, 100 % natural abundance). Attempt has been made to develop different radiochemical separation technique for isolation of NCA Tc radionuclides from the bulk target matrix [53,54].…”
Section: Protocol and Physics Of Heavy Ion Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a decade, our continuous endeavour was to use green chemistry mandates in radiochemical experiments 20 . Earlier, in 'Radio-green Chemistry' experiments we have used many environmental friendly benign bio reagents like Poly (N-vinylpyrrolidone) [21][22] , polyethylene glycol [23][24] and many plant biomaterials [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Roger et al reported the partitioning behavior of pertechnetate using a PEG-ABS system. 3,5,6 Over the last ten years, our laboratory has made continuous endeavors to develop new green separation methodologies, using aqueous biphasic systems [7][8][9][10][11][12][13][14][15][16] or other environmentally benign reagents such as polyvinylpyrrolidone 17,18 and ionic liquids. 19 In this study, we made an attempt to separate Ru and Tc radionuclides from bulk yttrium target.…”
Section: Introductionmentioning
confidence: 99%